2002
DOI: 10.1021/np0103113
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Guaianolides and a Fulvenoguaianolide from Artemisia myriantha

Abstract: The aerial parts of Artemisia myriantha have afforded one new fulvenoguaianolide and four dimeric guaianolides in addition to seven known guaianolides. The structures of all the compounds were elucidated by 2D NMR. It is speculated that the dimeric guianolides are formed via Diels-Alder type reactions of fulvenoguaianolide derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…8 The requisite allyl vinyl ether precursor in these reactions is produced as a transient species through a 5-exo dig process involving the intramolecular addition of an alkoxide moiety to a proximal triple bond. Under high-temperature conditions -most conveniently achieved using microwave irradiation-this intermediate rearranges directly to afford a cyclohept-4-enone derivative via the [3,3] cyclizations of acetylenic alcohols has been amply documented, 9 the formation of 2-alkylidenetetrahydrofurans by intramolecular addition of an alkoxide moiety to triple bonds is much less common.Investigations conducted in our laboratory to date have involved tertiary acetylenic alcohols, which seem particularly well suited as precursors for the cyclization/Claisen sequence. In this note, we wish to report a useful and practical extension of this methodology, which takes advantage of secondary 4-pentyn-1-ol systems as precursors a variety of substituted sevenmembered ring containing compounds, particularly mono-and bicyclic αβ-disubstituted 4-cycloheptenone derivatives according to the general strategy depicted in Scheme 1.…”
mentioning
confidence: 99%
“…8 The requisite allyl vinyl ether precursor in these reactions is produced as a transient species through a 5-exo dig process involving the intramolecular addition of an alkoxide moiety to a proximal triple bond. Under high-temperature conditions -most conveniently achieved using microwave irradiation-this intermediate rearranges directly to afford a cyclohept-4-enone derivative via the [3,3] cyclizations of acetylenic alcohols has been amply documented, 9 the formation of 2-alkylidenetetrahydrofurans by intramolecular addition of an alkoxide moiety to triple bonds is much less common.Investigations conducted in our laboratory to date have involved tertiary acetylenic alcohols, which seem particularly well suited as precursors for the cyclization/Claisen sequence. In this note, we wish to report a useful and practical extension of this methodology, which takes advantage of secondary 4-pentyn-1-ol systems as precursors a variety of substituted sevenmembered ring containing compounds, particularly mono-and bicyclic αβ-disubstituted 4-cycloheptenone derivatives according to the general strategy depicted in Scheme 1.…”
mentioning
confidence: 99%
“…[15] They are known to be potent histamine liberators and selective inhibitors of sarcoendoplasmic reticulum Ca 2+ AT P dependent pumps (SERCAs). Two more guaianolides, arglabin (42) [16] and ixerin Y (43) [17] having the 5,7,5-tricyclic ring system, exhibit strong activities against breast, colon, ovarian, and lung cancers.…”
Section: Domino Enyne/rcm Reactionmentioning
confidence: 99%
“…Structures of biologically important oxaand dioxa-triquinanes like anislactone A (13) and B (14), [8] merrilactone A (15), [9] isogenine (16) [10] and C-norcardanolide (17) [11] are shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…and Kir. (Adekenov et al, 1993;Bottex-Gauthier et al, 1993;Shaikenov et al, 2001;Wong et Brown, 2002). Kinetic studies showed that the phosphorylated form of Arglabin-DMA (a water-soluble form of arglabin) competitively inhibited the binding of farnesyl diphosphate to farnesyltransfrase (FTase) (End, 1999;Shaikenov et al, 2001).…”
Section: Introductionmentioning
confidence: 99%